PERSEPSI PETERNAK TERHADAP PEMANFAATAN SAPI SEBAGAI ATRAKSI WISATA DI KABUPATEN TABANAN, BALI - Inggriati N. W. T; I G. Suarta; D. A. Warmadewi (Fakultas Peternakan Universitas Udayana, 2019)
The study aims at determining the level of behavior and cattle farmers expectation for using cattle as agro touristattraction, analyze the cattle breeders income and the relationship between breeders behavior and expectationincluding their perception of agro-tourism activities using cattle as attraction. It was conducted at Penebel andMarga districts, Tabanan regency. The respondents were collected as quota; 50 breeders were interviewed in 6agro-tourism places such as Somya Pertiwi and Jatiluwih, Taman Sari Buana, Rumah Desa, tourist village of Pinge,and Cau Coklat. The data was analyzed in descriptive qualitative and correlation analysis. It showed that 1) farmersbehavior towards the existence of agro-tourism using cattle as tourist attraction considered to be good; 2) income offarmers participation using cattle as tourist attraction range between Rp. 50.000 - and Rp. 300.000,- in ploughingactivity, and 3) positive relationship between farmers behavior and expectation and their perception towards thedevelopment of agro-tourism business who use cattle as attraction. It can be concluded that 1) breeders have goodbehavior towards the development of agro-tourism business; 2) breeders gained extra income by participating inagro-tourism activities in order to achieve income by selling their cattle; 3) breeders have better behavior and higherexpectation which is the better perception towards the use of cattle in agro-tourism business activities. Finally,suggestions such as 1) investors in agro-tourism business should co-operate with famers in their surroundingsto run the activities; 2) Breeders should encourage raising cows instead of bulls since they are tame and increasepopulation of cattle in their area; 3) local government should play important role in development of agro-tourismbusiness i.e. village roads construction so it can encourage the visitors to come to the location. All of those willpositively affect the prosperity of local breeders